Genetic variation in PCAF, a key mediator in epigenetics, is associated with reduced vascular morbidity and mortality: evidence for a new concept from three independent prospective studies. Issue 2 (8th November 2010) - Pons, Douwe; Trompet, Stella; de Craen, Anton J M; Thijssen, Peter E; Quax, Paul H A; de Vries, Margreet R; Wierda, Rutger J; van den Elsen, Peter J; Monraats, Pascalle S; Ewing, Mark M; Heijmans, Bastiaan T; Slagboom, P Eline; et al.
Abstract : Aims: This study was designed to investigate the counterbalancing influence of genetic variation in the promoter of the gene encoding P300/CBP associated factor (PCAF), a lysine acetyltransferase (KAT), on coronary heart disease (CHD) and mortality. Methods and results: The association of genetic variation in the PCAF-gene with CHD, restenosis and mortality was investigated in three large cohorts. The results were combined to examine overall effects on CHD mortality and on restenosis risk. Compared with the homozygous −2481G allele in the PCAF promoter, a significant reduction in CHD mortality risk with the homozygous −2481C PCAF promoter allele was observed. A combined risk reduction for CHD death for the three studies was 21% (15–26%; p=8.1×10 –4 ). In elderly patients (>58 years) the effects were stronger. Furthermore, this PCAF allele was significantly associated with all-cause mortality (p=0.001). Functional analysis showed that nuclear factors interact in vitro with the oligonucleotides encompassing the −2481G/C polymorphism and that this interaction might be influenced by this polymorphism in the PCAF promoter. Moreover, modulation of PCAF gene expression was detectable upon cuff-placement in an animal model of reactive stenosis. Conclusion: We showed in three large prospective studies that the −2481C allele in the PCAF promoter is associated with a significant survival advantage in elderly patients. Our observations promote the concept that epigenetic processes are under genetic control and that, other than environment, variation in genes encoding KATs may also determine susceptibility to CHD outcomes and mortality.